2020
DOI: 10.1159/000505549
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tanycytes: Balance between Efficiency and Specificity

Abstract: Tanycytes are peculiar ependymoglial cells lining the bottom and the lateral wall of the third ventricle. For a decade, the utilization of molecular genetic approaches allowed us to make important discoveries about their diverse physiological functions. Here, I review the current methods used to target tanycytes, focusing on their specificity, their efficiency, their limitations, as well as their potential future improvements.specificity? This mini-review aims to describe the current methods used to selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Tanycytes are nowadays recognized as potential targets in therapeutics for obesity and metabolic-related diseases, and future works plan to optimize their targeting (101). This interest first relies on the fact that the reactivation of tanycyte functions in pathological conditions, in particular the reactivation of ERK signaling (27,79), improves the physiological state of the individual.…”
Section: The Potential Role Of Tanycytes In Metabolic Diseases and Therapeutic Perspectivesmentioning
confidence: 99%
“…Tanycytes are nowadays recognized as potential targets in therapeutics for obesity and metabolic-related diseases, and future works plan to optimize their targeting (101). This interest first relies on the fact that the reactivation of tanycyte functions in pathological conditions, in particular the reactivation of ERK signaling (27,79), improves the physiological state of the individual.…”
Section: The Potential Role Of Tanycytes In Metabolic Diseases and Therapeutic Perspectivesmentioning
confidence: 99%
“…5f). This result was somewhat unexpected, because transcriptional continuity was previously thought to exist only between spatially neighboring tanycyte subtypes 38,55 . A more recent study provided evidence that β1 tanycytes exhibit some transcriptional continuity with both α1 and α2 tanycytes, but also indicated that β2 tanycytes were non-overlapping and transcriptionally distinct 36 .…”
Section: Eschr Captures Cell Types and Continuity In Static Adult Tissuementioning
confidence: 88%
“…5a) 54 . More recent studies have suggested that many of these properties may exhibit substantial continuity between and within each of these subtypes [36][37][38][39][40]55 . However, individual tanycyte scRNA-seq studies and an integrated analysis of these datasets all reported discrete groupings of tanycytes defined by hard clustering approaches 37,39,56,57,58 , with no insight into the robustness of these assignments and whether there is overlap or continuity between them.…”
Section: Eschr Captures Cell Types and Continuity In Static Adult Tissuementioning
confidence: 99%
“…Next, using a microinjection syringe pump (WPI, # UMP3T-1), 2 μL of the AAV control AAV 1 -mCherry-U6>Scramble (Vector Builder, ID: VB010000-0024wah, title, >10 12 G) or G6pt knockdown AAV 1 -mCherry-U6>m Slc37a4 (Vector Builder, ID: VB210324-1260vvu, title, >10 12 G) were infused into the 3 V (anteroposterior, −1.8 mm; midline, 0 mm; dorsoventral, −5.5 mm). It is important to mention that serotype 1 AAVs do not traverse the parenchyma and, moreover, can specifically infect tanycytes [ 17 ]. All experiments were performed at 4 weeks post-transduction, and analgesia was applied following the previously described recommendations [ 18 ].…”
Section: Methodsmentioning
confidence: 99%